Non-financial Information Assurance: A Review of the Literature and Directions for Future Research - Azantouti, Asem Saad Ali (Auckland University of Technology, 2022)
Corporate non-financial information reporting, in the form of sustainability reports (GRI, 2013) and integrated reports (IIRC, 2017), is now a globally established practice (KPMG, 2020). However, stakeholders remain sceptical as to the credibility of these disclosures labelling them as nothing more than corporate green wash (Farooq & De Villiers, 2017, 2018). In response some reporters procure external assurance over their disclosures (Farooq & De Villiers, 2018, 2019). This phenomenon has attracted scholars’ attention and there now exists a growing body of literature examining this new form of assurance (Amran & Devi, 2008). The purpose of this study is to review the literature on non-financial information assurance and to address three inter-related research objectives. First, to assess the current state of academic research in the field by analysing researchers, journals, themes, research methods and theories. Second, to understand the nature of non-financial assurance engagements by structuring the literature around the definition of an assurance engagement (IAASB, 2013, p.7). This definition comprises of five key elements including: (1) a tripartite arrangement, (2) subject matter of assurance, (3) a suitable criterion, (4) sufficient appropriate evidence, and (5) a written assurance report. A combined theoretical lens of accountability and capture to analyse this second research question. Finally, to identify gaps in the literature and provide directions for future research. The study adopts Massaro, Dumay and Guthrie’s (2016) 10 step approach to undertaking a structured literature review. Following this approach, a total of 170 articles were identified, published from 1999 to 2021. These articles were analysed to address the three research objectives. The study offers several academic and practical contributions. Researchers will benefit from an overview of the literature and guidance on avenues for future research. Auditing lecturers can use the findings from this study to develop content for their courses (e.g., contemporary issues in auditing). This is important given that accounting firms (particularly the Big Four) control a significant share of the market for non-financial assurance engagements Reporting entities, seeking assurance over their non-financial disclosures, will gain from a better understanding of this new form of assurance. Regulatory bodies can use the insights from this study to better inform policy and regulations, such as revising corporate governance codes to encourage non-financial assurance. Assurance practitioners may benefit from the insights offered by scholars, as well as using the literature review to identify research of particular interest.